Deciphering air colors - Malikova P.M Маликова П.М; Zhuparkhan B Жупархан Б (Рroblems of engineering and professional education, 2023)
In this article deshifrirovaniye of aerial photographs are considered. As the deshifrirovaniye of aeromnik gives full information on the contents and nature of objects and an earth contour in a picture, these values give the sizes, volumes, types of the image